What Context Matters and at What Level? A Test of Racial/Ethnic Threat, Symbolic Threat, and Structural Inequality Perspectives in Juvenile Court Decision-Making - Leiber, Michael J. (Crime & delinquency, 2021)
Do traditional theories of conflict influence juvenile court decision-making and explain racial/ethnic disparities? Racial/ethnic threat, symbolic threat, and structural inequality perspectives purport social controls increase when groups differ in race, ethnicity, or class. Scholarship tends to test one perspective at a time and use county as a unit of analysis. Taking a comparative approach, this study evaluates whether contextual indicators of these three theories, measured at the county- and zip code-levels, contribute to Black-White and Latino-White disparities in court decisions. Multilevel models reveal weak and partial support for each perspective. More effects appear at the zip code-level, indicating conflict may occur within rather than across courts. Macro-level theories must then be reconsidered to describe modern-day juvenile court proceedings.